Some cashmere characteristics of hair goats raised in Van province - Tuncer, Selçuk S. (Austral Journal of Veterinary Sciences, 2018)
The aim of this study was to uncover certain physical properties of cashmere fibres obtained from goat hair in Van, Turkey, and determine their usability in the textile sector. For this purpose 36 hair goats were studied, aged between two and three years old, obtained from breeders at Van Yüzüncü Yıl University Livestock Facilities and the Özalp and Başkale districts of Van, with twelve goats being taken from each breeder. The sample of hairs were collected by combing three areas of the goat’s body (shoulder, flank and rump). The analysis indicated that the cashmere length of two-year-old hair goats was longer than that of three-year-old hair goats. There was no linear relationship between the differences among cashmere elasticity and yield properties and the altitude levels of the districts. It was determined that the fibre diameter of the cashmere of hair goats in Van was acceptable for the textile sector and competitive with major cashmere-producing countries.